Biotechnological applications from a Leishmania amastigote-specific hypothetical protein in the canine and human visceral leishmaniasis. (October 2020) - Oliveira-da-Silva, João A.; Machado, Amanda S.; Tavares, Grasiele S.V.; Ramos, Fernanda F.; Lage, Daniela P.; Ludolf, Fernanda; Steiner, Bethina T.; Reis, Thiago A.R.; Santos, Thaís T.O.; Costa, Lourena E.; Bandeira, Raquel S.; Martins, Vívian T.; et al.
Abstract: The treatment against visceral leishmaniasis (VL) presents problems, mainly related to the toxicity and/or high cost of the drugs. In this context, a rapid and precise diagnosis of the disease should be performed, mainly to treat patients as soon as possible, aiming to reduce the treatment time and the toxicity of the therapeutics. In the present study, the diagnostic role of an amastigote-specific Leishmania protein was evaluated in the canine and human VL. Results showed that the recombinant protein (called rLiHyJ) and one specific B cell epitope (called PeptJ) predicted from protein sequence presented high sensitivity and specificity values to diagnose canine and human disease, showing also a low reactivity against cross-reactive samples. The rA2 protein and a parasite antigenic extract showed variable sensitivity and/or specificity values in the ELISA experiments. A prognostic evaluation of protein and peptide in the human VL indicated that specific IgG antibodies significantly decreased after treatment, when compared to be values obtained before therapy. The in vitro immunogenicity using rLiHyJ in peripheral blood mononuclear cell (PBMC) cultures collected of such patients and healthy subjects suggested that the protein induced lymphoproliferation and high IFN-γ production in the stimulated cells. In conclusion, although preliminary, results suggest that rLiHyJ and PeptJ could present distinct biotechnological applications in the canine and human VL. Graphical abstract: Image 1 Highlights: The diagnostic efficacy of rLiHyJ and PeptJ was evaluated in the visceral leishmaniasis. High sensitivity and specificity was found when canine and human sera were used. A Th1-type immunogenicity induced by rLiHyJ was found in human PBMCs. The post-therapeutic follow-up showed a drop in the anti-rLiHyJ antibody levels. The protein shows immunogenic, diagnostic and prognostic potential.